1633. Improving the diagnosis of extra-pulmonary tuberculosis (EPTB): experience from north India. (31st December 2020) - Sharma, Anchal; Sharma, Kusum; Modi, Manish; Sharma, Aman
Abstract: Background: Rapid and accurate diagnosis of extra-pulmonary tuberculosis (EPTB) is imperative for early treatment and better patient outcome. Loop-mediated Isothermal Amplification (LAMP) is a promising nucleic-acid amplification assay. LAMP assay could be carried out in simple water bath under isothermal conditions in 60 minutes, and can be performed in any laboratory even in rural setting in resource poor endemic countries. We evaluated LAMP assay using two different target regions LAMP primers specific for Mycobacterium tuberculosis complex for the diagnosis of EPTB. Methods: LAMP assay using 6 primers (each for IS 6110 and IS1081) specific for Mycobacterium tuberculosis complex were performed on patients suspected of EPTB on various EPTB samples(CSF, Synovial fluid, Lymaphnode and tissue biopsies and various other samples) of 150 patients (50 confirmed, 100 suspected) Clinically suspected of EPTB and 100 non-TB control subjects. Results: Overall LAMP test (using any of the two targets) had sensitivity and specificity of 96% and 100% for confirmed (50 culture positive) EPTB cases. In 100 clinically suspected but unconfirmed EPTB cases, LAMP was positive in 87 out of 100 cases (87%). Sensitivity of IS 6110 LAMP, 1S1081 LAMP and IS 6110 PCR for clinically suspected cases was 78 (78%), 84 (84%) and 70 (70%), respectively. In total 150 EPTB patients, the overall sensitivity of microscopy, culture, IS 6110 PCR, IS 6110 LAMP, 1081 LAMP and the LAMP test (if any of the two targets were used) were 4%, 33.3%, 74.6%, 82.66%, 87% and 92%, respectively. Specificity of all the tests was 100%. There were 8 cases which were missed by IS 6110 LAMP and 2 cases by 1081 LAMP. Conclusion: LAMP assay using two targets is a promising technique for rapid diagnosis of EPTB in 60 minutes especially in a resource poor setting who are still battling with this deadly disease. Disclosures: All Authors : No reported disclosures